2016
DOI: 10.1186/s12866-016-0762-z
|View full text |Cite
|
Sign up to set email alerts
|

Consensus computational network analysis for identifying candidate outer membrane proteins from Borrelia spirochetes

Abstract: BackgroundSimilar to Gram-negative organisms, Borrelia spirochetes are dual-membrane organisms with both an inner and outer membrane. Although the outer membrane contains integral membrane proteins, few of the borrelial outer membrane proteins (OMPs) have been identified and characterized to date. Therefore, we utilized a consensus computational network analysis to identify novel borrelial OMPs.ResultsUsing a series of computer-based algorithms, we selected all protein-encoding sequences predicted to be OM-loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 115 publications
5
31
0
Order By: Relevance
“…The genes encoding these OMPs were recently shown to be cotranscribed (32,35), suggesting that these OMPs would be coexpressed. However, in this study, we observed a difference in the temporal antibody response to the individual BB0405 and BB0406 OMPs, suggesting that they may not be coordinately expressed during infection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The genes encoding these OMPs were recently shown to be cotranscribed (32,35), suggesting that these OMPs would be coexpressed. However, in this study, we observed a difference in the temporal antibody response to the individual BB0405 and BB0406 OMPs, suggesting that they may not be coordinately expressed during infection.…”
Section: Discussionmentioning
confidence: 99%
“…Outer membrane protein BB0405 was initially identified in a screen for outer surface proteins (34) and was more recently characterized for its physicochemical properties (32) and role in B. burgdorferi virulence (35). Additional studies on BB0405 orthologs of other borrelial genospecies have indicated that this OMP binds human factor H (36,37), suggesting that BB0405 and its orthologs play a role in serum resistance.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to Lmp1, P66, and enolase, two other chromosomally encoded proteins (outer membrane proteins), BB0838 and BB0465, were also mapped by PA peptides. BB0838, mapped by p202B71, is a 120-kDa outer membrane protein which was experimentally demonstrated to be surface exposed (99). The fact that no transposon was inserted in the bb0838 gene upon global transposon mutagenesis (100, 101) strongly suggests that BB0838 plays an essential role in the life cycle of B. burgdorferi.…”
Section: Figmentioning
confidence: 99%